Clinical Course and Predictors of Subsequent Recurrence and Survival of Patients With Ipsilateral Breast Tumor Recurrence - Soo Yeon Baek MD; Jisun Kim MD, PhD; Il Yong Chung MD, PhD; Beom Seok Ko MD, PhD; Hee Jeong Kim MD, PhD; Jong Won Lee MD, PhD; Byung Ho Son MD, PhD; Sei-Hyun Ahn MD, PhD; Sae Byul Lee MD, PhD (Cancer Control, 2022)
Purpose To evaluate the clinical course and long-term outcomes of patients with ipsilateral breast tumor recurrence (IBTR) after breast-conserving surgery (BCS) and identify independent prognostic factors for further recurrence. Methods In this retrospective study, we reviewed the records of 327 patients who experienced IBTR after undergoing BCS for breast cancer at Asan Medical Center during 1990–2013. Overall survival (OS) after IBTR and cumulative incidence rates of recurrences after IBTR were calculated. The association of clinicopathological factors with survival and the development of further recurrence after IBTR was determined in multivariate analysis. Results At a median follow-up of 127.7 months, 97 patients experienced recurrence after IBTR. The 5-year and 10-year cumulative incidence rates of recurrence after IBTR were 32% and 41%, respectively. The 5-year and 10-year OS rates after IBTR were 86.6% and 70.3%, respectively. In multivariate analysis, hormone receptor negativity was associated with decreases in OS after IBTR (hazard ratio [HR] 2.83, 95% confidence interval [CI] 1.18–6.78). Patients with longer disease-free interval (DFI) had decreased risks of second recurrence (HR .99, 95% CI .99–1.00), and second locoregional recurrence (LRR) (HR .98, 95% CI .97–.99). Lymphovascular invasion (LVI) of IBTR was associated with increased recurrence rates (second recurrence-free survival, HR 3.58, 95% CI 2.16–5.94; second LRR free survival, HR 5.21, 95% CI 2.77–9.78; second distant metastasis-free survival, 2.11, 95% CI 1.04–4.30) and lower survival rates (OS after IBTR, HR 4.64, 95% CI 2.23–9.67). Conclusions Despite subsequent recurrences during long-term follow-up, the survival rates after IBTR remained high. Patients with hormone receptor-negative tumors, shorter DFI, and tumors that present LVI of IBTR had higher risks for recurrence and poor survival rates after IBTR. The study findings may help in understanding the course and prognosis of IBTR patients and identifying high-risk IBTR to establish management strategies.